Simple methodology for the therapeutic drug monitoring of the tyrosine kinase inhibitors dasatinib and imatinib. (6th August 2012) - Birch, M.; Morgan, P. E.; Handley, S.; Ho, A.; Ireland, R.; Flanagan, R. J.
ABSTRACT: A simple HPLC method has been developed to measure imatinib and N ‐desmethylimatinib (norimatinib) in plasma or serum at concentrations attained during therapy. Adaptation of this method to LC‐MS/MS also allows dasatinib assay. A small sample volume (100 μL HPLC‐UV, 50 μL LC‐MS/MS) is required and analysis time is <5 min in each case. Detection was by UV (270 nm) or selective reaction monitoring (two transitions per analyte) tandem mass spectrometry. Assay calibration was linear (0.05–10 mg/L imatinib, 0.01–2.0 mg/L norimatinib and 1–200 µg/L dasatinib), with acceptable accuracy (86–114%) and precision (<14% RSD) for both methods. A comparison between whole blood and plasma confirmed that plasma is the preferred sample for imatinib and norimatinib assay. For dasatinib, although whole blood concentrations were slightly higher, plasma is still the preferred sample. Despite considerable variation in the (median, range) plasma imatinib and norimatinib concentrations in patient samples [1.66 (0.02–4.96) and 0.32 (0.01–0.99) mg/L, respectively, N = 104], plasma imatinib was >1 mg/L (suggested target for response) in all but one sample from patients achieving complete molecular response. As to dasatinib, the median (range) plasma dasatinib concentration was 13 (2‐143) µg/L ( N = 33). More observations are needed to properly assess the potential role of therapeutic drug monitoring in guiding treatment with dasatinib. Copyright © 2012 John Wiley & Sons, Ltd.